Differential perceptions regarding personal protective equipment use during the COVID-19 pandemic by NHS healthcare professionals based on ethnicity, sex and professional experience - Tim Robbins; Ioannis Kyrou; Maariyah Vankad; Risheka Suthantirakumar; Natalie Igharo; Kiran Patel; Harpal Randeva; Sailesh Sankar (Elsevier, 2021)
Summary: Objectives: To capture perceptions regarding personal protective equipment (PPE) among healthcare professionals during the COVID-19 pandemic, including staff subgroups at high risk for severe COVID-19, such as black and minority ethnic (BAME) groups. Design: Electronically distributed survey with semi-quantitative analysis. Survey distributed at a major academic NHS tertiary referral centre in the West Midlands with a diverse medical workforce to medically qualified staff who completed COVID-19 redeployment training. (N=121; 47% female; 49% of BAME background; 26% international medical graduates). Results: All demographic groups reported overall good awareness of when and how to use PPE during COVID-19 pandemic. Statistically significant differences in the perceptions regarding PPE use during COVID-19 were noted between BAME vs non-BAME staff, international vs UK medical graduates, and male vs female participants, as well as between professionals at different stages of their career. The differences related to perceptions around availability, degree of protection provided, perceived inconvenience, ability to raise concerns about availability, confidence in sharing underlying health conditions with managers and the impact of full PPE in emergency situations causing delay patient care. Conclusions: Amongst medically qualified staff, significant differences exist in the perceptions relating to the, availability and effectiveness of PPE during the COVID-19 pandemic depending on country of training, ethnic background and sex. GAFREC Study Approval: Study ID GF0392.